Effects of forestry activities on surface water quality in the Pacific region: a case study of the Rewa River catchment, Fiji Islands. (1st December 2002) - Carpenter, C.; Lawedrau, A.
A large proportion of the world's population is supported by the Pacific Region, from as far south as New Zealand, reaching the coastlines of China. Over the last 50 years, there has been a marked increase in this region in terms of agricultural productivity, industrial activities and not least, in the regional population (Naidu et al., 1997). Such changes can have profound effects on forest resources and associated issues related to water quality and availability.